4=-6v+8(v+2)

Simple and best practice solution for 4=-6v+8(v+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4=-6v+8(v+2) equation:


Simplifying
4 = -6v + 8(v + 2)

Reorder the terms:
4 = -6v + 8(2 + v)
4 = -6v + (2 * 8 + v * 8)
4 = -6v + (16 + 8v)

Reorder the terms:
4 = 16 + -6v + 8v

Combine like terms: -6v + 8v = 2v
4 = 16 + 2v

Solving
4 = 16 + 2v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-2v' to each side of the equation.
4 + -2v = 16 + 2v + -2v

Combine like terms: 2v + -2v = 0
4 + -2v = 16 + 0
4 + -2v = 16

Add '-4' to each side of the equation.
4 + -4 + -2v = 16 + -4

Combine like terms: 4 + -4 = 0
0 + -2v = 16 + -4
-2v = 16 + -4

Combine like terms: 16 + -4 = 12
-2v = 12

Divide each side by '-2'.
v = -6

Simplifying
v = -6

See similar equations:

| -8x+4(x-3)=-8 | | 8y+8y=24 | | -5x+3=-47 | | -75+4x+6x=25 | | Y(2)+3y(2-1)=e(2) | | Y(1)+3y(1-1)=e(1) | | 5x-3x-19=11 | | 81+w=10w | | 12u=24+9u | | 5(3y-4)=10 | | 4s+3s-9s=22 | | 4=10m | | -6x-2x=48 | | Y(0)+3y(0-1)=e(0) | | 30=9m | | (-9p-1)-(-2p-5)= | | b/10=20 | | 6u=1+3 | | -7(-m-3)=46 | | 5(x+0.40)=5 | | 6x-6=-24+2x | | X+9+(-11)=2 | | (5-2i)/(1-3i) | | 56=5w+16 | | -2+3y=-23 | | 26=x/4-17 | | cot(10x)=cot(5x) | | 5x(4.1+b)=45 | | tan(10x)=tan(5x) | | 67.2=3.5*q | | 150-20x+6x=6+11 | | -2m=-9 |

Equations solver categories